Kinetics study of microwave-assisted solvent extraction of oil from olive cake using hexane : Comparison with the conventional extraction - Amarni, Fatiha; Kadi, Hocine (Innovative food science & emerging technologies, 2010)
Microwave-assisted solvent extraction (MASE) of oil from olive cake can be used as an alternative for conventional solvent extraction (CSE).The present research showed that, compared to the CSE, the MASE gave better yields within very short times. The results obtained with this new procedure indicated that the radiation power and exposition time enhanced extraction ability. The Patricelli model has been applied to describe the MASE kinetic. The coefficients of determination were found to be very high in all the cases (R ² ≥0.992) indicating a good fit of the experimental data at tested conditions. The results obtained were compared with those given by the same model in the case of the conventional extraction. Industrial relevance: Olive cake pollutes the environment around the Mediterranean basin where it is generated in great amounts within a short period (from November to March). To avoid this pollution, it must be treated. Its valorization by recovery of its residual oil using conventional solvent extraction is time-consuming and needs large volumes of solvent. Compared to this conventional technique, the microwave-assisted solvent extraction can be a nice alternative because it gives better yields within short times and consumes less solvent.